Characterization and refinement of zein-based gels. (April 2020) - Gagliardi, Agnese; Froiio, Francesca; Salvatici, Maria Cristina; Paolino, Donatella; Fresta, Massimo; Cosco, Donato
Abstract: Biopolymer-based gels have a significant impact on controlling rheological properties in a number of industrial processes. Many natural polymers such as animal and plant proteins are used as gelling agents. In particular, zein is a biocompatible protein that embraces almost 80% of the whole protein content of corn. The current study was designed to characterize various gels made up of zein, in order to provide useful formulations for various applications. Diffusing wave spectroscopy in association with dynamic rheology was used to obtain a full physico-chemical characterization of the zein dispersions. Zein gels were prepared using different amounts of protein (10%, 12.5%, 15% and 20% w/v) and their stability was evaluated by Turbiscan Lab®. The microrheological parameters e.g. SLB (solid-liquid balance), EI (elasticity index), MVI (macroscopic viscosity index) and the storage (G′) and loss (G″) moduli were evaluated as a function of strain, frequency, time, and temperature providing information on the linear viscoelastic region, structural assembly, and thermal characteristics. The formulations containing 15% and 20% w/v of zein formed stable dispersions especially at 37 °C. The high protein concentration showed storage moduli values significantly greater than those of viscous moduli, demonstrating that the elastic character became dominant. These findings were confirmed up to 50 °C. The viscosity of these samples decreased as the shear rate increased, thus demonstrating a typical pseudoplastic or shear thinning behavior. Our findings showed that dispersions containing 20% w/v of zein are promising low-cost formulations to be used as a gel in various fields of application. Graphical abstract: Image 1 Highlights: The formulations containing 15% and 20% w/v of raw zein formed stable dispersions. The high protein concentration promoted a typical pseudoplastic behavior. Gels containing 20% w/v of raw zein are promising low-cost formulations.